The Effect of Verbalising and Voluntary Movements on Left Hemisphere - Hapsari, Anggita (ANIMA Indonesian Psychological Journal, 2008)
The aim of this study was to examine the interference effect of a verbal task and a tap task (voluntary movement) on the left hemisphere. The participants (N = 6; 4 females and 2 males) are psychology students. This present study excluded the left-handed. As part of a between subject de- sign, the participants were randomly assigned into two groups and each group did the experiment twice. The hypothesis that right-handed students who were only tapping (the control group) would have higher overall mean than when students were tapping and at the same time verbalising (the expe- rimental group) is not reflected by the results. It was concluded that verbal and voluntary movement tasks did not have interference effects on the left hemisphere, though the overall mean gained for the experimental group were slightly higher than the control group, i.e. 8.333 and 8.167, respectively. Tujuan studi ini adalah mencermati akibat interferensi tugas verbal dan tugas tepukan (ge- rakan volunter) terhadap hemisfer kiri. Para peserta (N = 6; 4 perempuan dan 2 pria) berasal dari kelas laboratorium psikologi, Universitas Massey. Studi ini tidak mengikusertakan yang kidal. Sebagai bagian dari desain antar-subjek, para partisipan dipilih secara acak dan dikelompokkan menjadi kelompok eksperimen dan kelompok kontrol, dan setiap kelompok melakukan percobaan dua kali. Hipotesis bahwa mahasiswa bukan kidal yang hanya menepuk (kelompok kontrol) mempunyai rerata menyeluruh yang lebih tinggi daripada mahasiswa yang melakukan keduanya, yaitu tugas menepuk dan tugas verbal sekaligus, tidak didukung oleh hasil studi. Disimpulkan tugas verbal dan tugas gerakan volunter tidak mengakibatkan interferensi pada hemisfer kiri, sekalipun rerata menyeluruh kelompok eksperimen agak lebih tinggi daripada kelompok kontrol, berturut-turut 8.333 dan 8.167